A simulation investigation on the effect of wheel-polygonal wear on dynamic vibration characteristics of the axle-box system. (September 2022) - Liao, Xiaokang; Yi, Cai; Zhang, Yi; Chen, Zili; Ou, Fengyu; Lin, Jianhui
Highlights: The paper integrated the flexible wheelset model calculated by the finite element method into the classical vehicle-track coupling dynamic model, and then imported the bearing substructure model into the vehicle-track coupling dynamic model including flexible wheelset to complete the bearing-vehicle-track coupled dynamic simulation model. In order to solve the contact relationship between raceway and roller, the slice method is used to describe the contact state of bearing substructure, and the contact between inner ring rib and roller is considered. To verify the correctness of the established bearing-vehicle-track model, field tests were conducted on the high-speed railway line from Beijing to Tianjin. The field tests verify the effectiveness of the simulation model as well as the correctness of the vehicle model under polygonal wheel wear excitation. The effects of the different orders and amplitudes of wheel-polygonal wear on dynamic performance of the axle-box system are analyzed and discussed in detail. Abstract: With the increasing speed of high-speed trains and the deteriorating operation environment of axle-box system, the dynamic performance of axle-box bearing directly affects the stability and safety of operation. In this paper, a bearing-vehicle-track coupling dynamic model is established, and its effectiveness is verified by field tests. The simulation results of the coupling dynamic model including wheel-polygonal wear show that the effect of high order polygonal wheel wear (17th ∼ 21st order) on the axle-box system is greater than that of low order wheel wear (1st ∼ 5th order). The frequency domain of axle-box vertical vibration acceleration excited by high order wheel-polygonal wear is mainly distributed in 400 ∼ 600 Hz. The low order polygonal wheel wear amplitude has little effect on the bearing roller-outer raceway contact load. When the wear amplitude of 20th order polygonal wheel is 0.06 mm, the roller-outer raceway contact load is 27.22% higher than that when the wear amplitude is 0.04 mm. In order to avoid bearing failure caused by excessive bearing roller-raceway contact force, the amplitude of 20th order polygonal wheel wear should reduce to less than 0.04 mm.